A espiritualidade franciscana em quatro imagens de São Francisco de Assis: a copresença da apresentação bizantina e da representação na nova arte - Cunha, Sintia Cristina da [UNIFESP] (2017)
It is well known that throughout the XIII century Italian painting underwent significant modifications in technical and conceptual terms. A painting inspired by a more incarnate figure concept, arises amidst the artistic context of Byzantine inspiration, aimed at the figuration of the spiritual world. However, the reasons for the flourishing of this "new art" are generally studied in relation to the changes that took place in the secular world, to the detriment of the religious. Therefore, such studies consider the changes from extrinsic factors to that of Christian spirituality, although the Middle Ages, as is also known, was a period immersed in such spirituality. In this way, it is proposed to study the change promoted by Saint Francis of Assisi in the way of experiencing medieval spirituality and how it probably reached artistic sensibility. The study is carried out through the analysis of four images of St. Francis of Assisi in Italy, related to the period in focus, since the saint at the same time that stimulated the representation of nature, had it expressed in his own image, they are: St. Francis in the fresco of the Santuario del Sacro Speco in Subiaco; in the tavola of the Bardi Chapel in Santa Croce in Florence; in the fresco of Cimabue, Our Lady with the child Jesus, four angels and St. Francis, in the lower Basilica of Assisi and, finally, in the fresco of Giotto, The dream of Pope Innocent III, in the upper Basilica of Assisi. Claiming greater emphasis on medieval religiosity in the West, I propose a more careful study of Byzantine participation in the process of artistic transformation. Such a process is usually understood through a logic of "overcoming" the old style that was characteristic of Italian Christian art, until now. However, in this dissertation this logic of "overcoming" will be questioned by the "conformity" between the new pictorial concept and the old style.